A Study on Social Internet of Vehicles - Jamsheera, M; Riyadh, M (International Journal of Computer Sciences and Engineering, 2025)
One of the main vision of Internet of Things (IoT) is to equip real-life physical objects with computing and communication power so that they can interact with each other for the social good. As one key members of IoT, Internet of Vehicles (IoV) has seen steep advancement in communication technologies. Here, a vehicle can easily exchange safe, efficient, infotainment, and comfort-related information with other vehicles and infrastructures using vehicular ad hoc networks (VANETs). We introduce a cloud-based VANETs theme to propose cyber-physical architecture for the Social IoV (SIoV). SIoV is a vehicular example of the Social IoT (SIoT), where vehicles are the key social members in the machine-to-machine vehicular social networks. We have identified the social structures of SIoV components, their relationships, and the interaction types that manage the overall system . Also we have defined the tNote message, that describes how vehicles can share transport related safe, efficient and comfort notes to the cloud and other infrastructure following the Dedicated Short Range Communication (DSRC) standard.